Analysis Of The Influence Of Product Attributes On Purchase Decisions For Asus Brand Laptops On Students Faculty Of Economics And Business Muhammadiyah University, Makassar - Moh Aris Pasigai; Aulia Aulia; Suarsi Suarsi (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine of the influence the exxent of the influence of product attributes which include (brand, proce, quality and design) on the decisions to purchase Asus brand laptops for students of the Facultyof Economics and Bussines, University of Muhammadiyah Makassar (a case study majoring, class of 2017). The type of research used with a quantitative approach. The data obtained is the result of the respondent’s interpretation studens majoring in management class 2017 as many 84 respondents. The analysis technique used in the study uses an interactive model with respondens , where the respondent’s interpretation data is then regulated by using data analysis tecniques in this case SPSS. Based on The research result obtained from processed data are that all design variabels have a more significant influence than all product attribute variabels, this is due to the regression equetion test the design variable value is greater and the averall variable value for marketing strategy.